A Study of Students’ Difficulties in Learning Selected Literature Subjects - Arsen Nahum Pasaribu; Jubilezer Sihite; Rizky Munthe (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This article is intended to find, to know and to find out what difficulties that are most often faced by students of the English literature study program in literature courses, especially literary genres and the factors that cause these difficulties in the English Literature study program, Faculty of Languages and Arts, University HKBP Nommensen Medan. In this study a qualitative descriptive research method was applied by describing the findings from the results of the analysis of the data obtained. The subjects of this study were the students of the fifth semester, Academic Year 2020 consisting of 20 students who were selected by using the cluster sampling technique. Data were collected from the results of filling out questionnaires and interviewing each student. The researcher distributed questionnaires to all class members. After that, the researcher selected ten students to be interviewed. The results of this study indicate that the difficulties experienced by students in literature courses can be classified into four sub-learnings namely prose, poetry, drama and folklore based on the semester lecture designs obtained. Apart from that, the factors that cause many students to experience difficulties in literature courses are because they often depend on other people, are not confident in delivering questions to the lecturers about the material, often have experience emotional disturbances when lectures take place, lecturers who teach the course explain the material too much fast, lack of respect and reinforcement for students and some of the students are not focused in lectures for various reasons.